Change in Cropping Pattern and Agriculture Productivity in Sidhmukh Canal Catchment Area: A Geographical Study of Hanumangarh District of Rajasthan: Exploring the Impact of Sidhmukh Canal on Cropping Patterns and Agriculture Productivity in Hanumangarh, Rajasthan (Journal of Advances and Scholarly Researches in Allied Education, 2019)
Job of agriculture stays imperative in empowering the State to accomplish and keep up nourishment self-sufficiency, particularly, in a poverty-stricken State. Supportable development of agriculture depends essentially on the procedure of horticultural change, which thus is very much associated with movements in cropping patterns. Lazy move in the cropping pattern towards non-sustenance grain crops in the State is because of moderate development of irrigation, low degree of fertilizer utilization, slow technology adoption and low degree of infrastructure. The lull during the time spent cropping pattern change implies that most government endeavors to diversify agriculture have neglected to take off. Covering just about seven districts of Rajasthan, the Sidhmukh canal has radically caused an adjustment in land use land spread. This examination focuses on Hanumangarh locale, which is beginning stage of Sidhmukh canal in Rajasthan. The land use and land spread pattern of an area is a result of the natural and financial factor and their usage by man in existence. The paper examines the structure and nature of Change in Cropping Pattern and Agriculture Productivity in Sidhmukh Canal Catchment Area.